The Sun Also Rises and As You Like It: a Study In Intertextuality: Exploring Intertextuality and Gender in The Sun Also Rises and As You Like It (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The Sun Also Rises(1926) and As You Like It (1599) are very similar to each other in more waysthan one.The two heroines represent in the respective ways the new woman oftheir times. Just as Hamlet is meant to represent the new man of theRenaissance, radically different from the Medieval man, so is Rosalind meant torepresent the new woman of the Renaissance as against the Medieval woman. Inthe same vien, if Jake Barnes represents the post-war generation of men, sodoes Brett Ashley represent the post-war generation of women. Here, the modernequivalent of the Medieval era is the Victorian period in England and thepuritan period in America, Both the heroines carry new confined, showingself-reliance, and fresh outlook free from the chains of orthodoxy andconstraints of tradition. Both, heroines become the touchstone for measuringdifferent characters of man. The fundamental similarity between As You Like Itand The Sun Also Rises is the juxtaposition, both thematic and structural,between the city and the country, including the values associated with the two.While in Shakespeare’s comedy, the opposition is set up between those in exilefrom the court and the natives of the Forest of Arden, in Hemingway’s comedy itis those hailing from Paris and the natives of Pamplona, a modern counterpartsof the Elizabethan pastoral. Intertextual studies reveals the dynamics ofjuxtaposition in the two text is, above all, a sense of the impermenance oflife that Lurks behind the mortal human life both at the court as well as thecountry in As You Like It and equally in Paris as well as Pamplona in The SunAlso Rises. In Shakespeare’s comedy, Jacque’s song on the seven stages of manremains un-erasable from the reader’s memory; it provides the back drop to allthe activities sequenced in the play that life is a stage, and man a mereplayer, acting out his role through the seven-scenes dividing earthly lifebecomes an unforgettable lessons, very much like “Ripeness is all” in KingLear, “Readiness is all” in Hamlet, and “Tomorrow and tomorrow and tomorrow” inMacbeth. It is in this view of life that both the comic, as well as the tragic,vision of Shakespeare come together in Hemingway’s The Sun Also Rises. As canbe seen intertextual study of two similar writers or texts can be rewarding inthat the effort leads to illuminating the historical conditions that createdthem as much as elucidating the texts or writers themselves.